How to write and publish a scientific paper - Gastel, Barbara; Day, Robert A. 1924-2021 (Greenwood, 2022)
"Thoroughly updated throughout, this classic, practical text on how to write and publish a scientific paper takes its own advice to be "as clear and simple as possible"--